A systematic literature review on the effects of risk management practices on the performance of Islamic banking institutions - Siti Najihah Noory; Shahida Shahimi; AbdulGhafar Ismail (Penerbit Universiti Kebangsaan Malaysia, 2021)
Risk management practices (RMPs) are important for Islamic banking institutions (IBIs) mainly because they represent the risk exposures that may affect their financial stability. The fact that RMPs is not a new activity in IBIs but still attract significant numbers of studies indicate the relevancy of the subject matter. For instance, weak risk management will hamper IBIs’ performance and eventually the stakeholders and industry at large. There are still lack of evidence on the effects of RMPs specifically on the IBIs given the nature and unique characteristics of the risks faced by these institutions. This systematic review article focuses on the effects of the RMPs on the performance of IBIs. Systematic literature review (SLR) is used in this study as it produces quality evidence on RMPs with more significant results on the effects of the IBIs’ performance. It defers greatly from the conventional literature review because the development of the systematic review is based on the main research question and utilized advanced search provided in the online journal databases. This study used eight (8) electronic journal databases and applied Preferred Reporting Items for Systematic review and Meta-Analysis (PRISMA). Based on the 39 primary studies related to RMPs and performance of IBIs, a total of 16 themes and 17 sub-themes were identified. The study finds that IBIs with good risk mitigation practices, risk management environment, policies and procedures, and risk monitoring have better financial performance. Hence, IBIs must ensure that RMPs a priority within the institutions to increase the financial performance and improve the overall competitiveness in the Islamic banking industry.